Effects of Selective Rehabilitation on Neck Pain due to Cervical Spondylosis - A Clinical Trial (Bangladesh Journal of Neuroscience, 2015)
Background:Pain in the neck is a common complaint of the patients attending the hospital. In clinical practice, neck pain is seen frequently as a presenting symptom and sometimes it becomes disabling and compromises the working capacity. One of the most common causes of pain in the neck is cervical spondylosis. Rehabilitation treatment may play an important role to improve the condition of the patients. For this purpose, the study was done to find out the effects of rehabilitation treatment on chronic neck pain to improve the present situation regarding treatment.Methodology: A randomized clinical trial was conducted in the department of Physical Medicine and Rehabilitation, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. A total of 150 patients were included and they were divided into two groups: group-A and group-B. Group-A was treated with selective rehabilitation and Group –B was treated with NSAID only. History, clinical examination and relevant investigations were done. The findings were recorded at first attendance and follow up was done weekly for six weeks. The results were expressed as mean ± SD and the level of significance was expressed by p-value unless otherwise stated. Student’s ‘t’ tests was done to test the hypothesis.Results: Among the study subjects 48(32 %)were male and 102 (68 %) were female. The male female ratio was 1: 2.12. There was significant improvement in both the group after treatment ( P= 0.001). But in comparison between two groups, all the baseline criteria were identical. There was no significant improvement between two groups up to 5th weak( P>05) but significant improvement was seen in Group-B than Group-A after six weeks treatment (P= 0.03). This results indicates that the improvement of the patient with cervical spondylosis was seen in selective rehabilitation group and in NSAIDs group. And improvementwas same in both the group up to 5th week and after six weeks more improvement was found in NSAIDs group.Conclusions: By this study, it may be concluded that to reduce symptom and disability, rehabilitation treatment can be used effectively for the treatment of chronic neck pain without analgesics and by this way nephropathy due to NSAIDs can be avoided.Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 102-109